1992
DOI: 10.1002/sia.740181205
|View full text |Cite
|
Sign up to set email alerts
|

Technique for XPS measurements of volatile adsorbed layers: Application to studies of sulphide flotation

Abstract: A system for treating XPS samples containing easily volatile and reactive adsorption layers is described. Desorg tion and reactions with atmospheric gases prior to the measurement are avoided by repeated exposure of the sample to an inert atmosphere at room temperature followed by cooling to liquid nitrogen temperature and sub sequent evacuation to spectrometer vacuum.The method has been applied to pyrite (FeS,) samples treated in aqueous potassium ethyl xanthate (dithiocarbonate) solutions. In agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…The lack of sample cooling in the introduction chamber (sample exposure time approximately ten minutes) can result in the loss of some S 0 through sublimation (Briggs and Seah, 1987;Kartio et al, 1992). Powder X-ray diffraction analysis of samples (leached using the identical experimental setup in pH one H 2 SO 4 solution with 12.4 g of added Fe 2 (SO 4 ) 3 at 85°C and a stirring speed of 500 rpm for 144 h) that were stored in the introduction chamber of the X-ray photoelectron spectrometer at a pressure of 10 )6 Torr for 12 h were found to retain a considerable component of crystalline S 0 (Harmer, 2002).…”
Section: Surface Analysismentioning
confidence: 99%
“…The lack of sample cooling in the introduction chamber (sample exposure time approximately ten minutes) can result in the loss of some S 0 through sublimation (Briggs and Seah, 1987;Kartio et al, 1992). Powder X-ray diffraction analysis of samples (leached using the identical experimental setup in pH one H 2 SO 4 solution with 12.4 g of added Fe 2 (SO 4 ) 3 at 85°C and a stirring speed of 500 rpm for 144 h) that were stored in the introduction chamber of the X-ray photoelectron spectrometer at a pressure of 10 )6 Torr for 12 h were found to retain a considerable component of crystalline S 0 (Harmer, 2002).…”
Section: Surface Analysismentioning
confidence: 99%
“…XPS spectra were collected on a Kratos Axis Ultra XPS using a monochromated Al-K a X-ray source (1486 eV). XPS samples in the analysis chamber at a pressure of 10 À9 Torr were not cooled, potentially causing the sublimation of elemental sulfur (Kartio et al, 1992). Surface charging effects were corrected using the aliphatic adventitious C(1s) peak at 284.6 eV.…”
Section: Oxidation Experimentsmentioning
confidence: 99%
“…Some studies have indicated that maximum xanthate adsorption occurs at low pH and may be due to the removal of surface oxidation in acidic solutions.1h3 Because the methods used to measure xanthate adsorption in those studies were indirect, namely measuring the amount of xanthate remaining in solution following the treatment of the pyrite, they are more subject to error because xanthate is known to decompose rapidly in solutions of low pH.23,24 Other studies have suggested that xanthate adsorption does not take place in the absence of oxidation products on the pyrite surface.4,6 Studies conducted in this laboratory have indicated that maximum Ñotation of mineral and coal pyrites in the presence of xanthate occurs at low pH, although direct evidence for xanthate adsorption under those conditions was not provided at the time.11 Evidence for xanthate adsorption on mineral pyrites at low pH has been obtained using XPS by monitoring changes in the C 1s, O 1s and S 2p peak envelopes, although it was necessary to cool the XPS sample holder with liquid nitrogen to obtain such evidence. 8,9 While the data in Tables 1, 2 and 4 do not show a direct correlation between the degree of pyrite surface oxidation and the F 1s peak intensity due to the adsorption of the Ñuoroxanthate, it is apparent that adsorption of Ñuoroxanthate is favored on pyrites with the least amount of surface oxidation. There has been general agreement from previous studies of xanthate adsorption onto mineral pyrites that the adsorption of the xanthate, usually in the form of dixanthogen, is facilitated by the presence of oxygen-containing groups on the pyrite surface.1h6,9 Such groups are : adsorbed OH~from the aqueous solutions,5,9 dissolved oxygen from oxygen-containing solutions1h3 or the oxosulfur products of pyrite oxidation such as and S 2 O 8 2Ĩ n this study, no attempt was made to purge S 2 O 7 2~.4,6 oxygen from the xanthate solutions.…”
Section: Discussionmentioning
confidence: 82%